(untitled) (Journal of science and technology exploration, 2026)
Culture is the soul of a nation. Amid the rapid advance of information technology, a global tide of digitization has swept across every field, making the deep convergence of culture and digital technology an historical inevitability. With keen foresight, the CPC Central Committee and the State Council have taken the major strategic decision to launch the National Cultural Digitization Initiative, charting a clear course for the high-quality development of China’s cultural sector and cultural industries. This paper probes the connotation and significance of the National Cultural Digitization Strategy, reviews the policy measures adopted by the central and local governments and their implementation, sums up current achievements and challenges, and looks ahead to future trends. It aims to provide useful reference for fully implementing the National Cultural Digitization Initiative and for accelerating the digital transformation of cultural industries and the building of a culturally strong country.